2017
DOI: 10.1002/ecs2.1734
|View full text |Cite
|
Sign up to set email alerts
|

Environmental indicators reflective of road design in a forested landscape

Abstract: Abstract. Roads cause both chemical and physical disturbance at the time of creation and through the maintenance of the road. However, none have fully considered the extent of above-and below-ground impacts related to roads. Our study seeks to fill this gap with three objectives: (1) quantify differences in the nematode community by road-use intensity, (2) estimate distance of environmental impact of roads using nematode community indices, and (3) relate nematode communities to abiotic soil and aboveground pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
0
10
0
4
Order By: Relevance
“…Significant correlations were identified using a Monte Carlo permutation test between the two resemblance matrices. Our approach was modelled after the application of the CoCA to identify associations between the plant communities and the soil microbial communities [47] and between the plant communities and the soil nematode communities [48]. All multivariate analyses were performed using CANOCO (version 5.04) [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant correlations were identified using a Monte Carlo permutation test between the two resemblance matrices. Our approach was modelled after the application of the CoCA to identify associations between the plant communities and the soil microbial communities [47] and between the plant communities and the soil nematode communities [48]. All multivariate analyses were performed using CANOCO (version 5.04) [49].…”
Section: Discussionmentioning
confidence: 99%
“…Areas damaged by windstorms are usually cleared; disturbed stands are harvested for economic (recouping financial losses before wood quality deteriorates) and sanitary (damaged trees can attract insects that can attack undisturbed trees in their neighborhood) reasons. Removal of the forest canopy dramatically alters the site microclimate, mainly light and water conditions [3], that lead to changes in the composition, diversity, and habitat structure of understory plant species, which have potential implications for the soil biota [48]. Any disturbance of the soil will lead to a succession in bacteria and fungi and the associated food web, with an initial decrease and then an increase in biodiversity [50], in agreement with the authors of Reference [16] who found that the characteristics of microbial activity (basal respiration, microbial biomass, N mineralization, and catalase activity) were significantly lower in the acidic soil of a cleared site of a Lariceto-Piceetum coniferous forest immediately after a windstorm.…”
Section: Discussionmentioning
confidence: 99%
“…Investigaciones recientes muestran que los indicadores ambientales presentan datos y comparaciones útiles para contribuir en la sostenibilidad de la naturaleza, en la toma de decisiones y formulación de políticas ambientales (Alphan, 2017;Neher et al, 2017;Nowak y Schneider, 2017;Pratama et al, 2017) y constituyen una herramienta básica de información y seguimiento de los procesos que se originan en el medio natural, social y económico (Xu y Zhang, 2013;Asumadu-Sarkodie y Owusu, 2017;Sinha et al, 2017).…”
Section: Indicadores Ambientales Espacio Temporalesunclassified
“…Los indicadores ambientales dan seguimiento al impacto ambiental biofísico y socioeconómico, reconocidos como una necesidad fundamental a nivel local, regional, nacional e incluso internacional (Neher et al, 2017;Sinha et al, 2017). Evalúa el impacto ambiental mediante herramientas innovadoras y precisas para predecir las consecuencias del desarrollo (Klug y Kmoch, 2015;Arnaiz-Schmitz et al, 2017;Han et al, 2017) proporcionando información útil para la planificación al presentar datos y comparaciones actualizados (Alphan, 2017;Gao et al, 2017;Luo et al, 2017;Bao y Zou, 2018).…”
Section: Indicadores Ambientales Espacio Temporalesunclassified
See 1 more Smart Citation